Seed maturity, germination, dormancy and storage of Melicope lunu-ankenda (Gaertn.) Hartley harvested at different maturity stages - Din Merican, Ariff Merican (2018)
Melicope lunu-ankenda, locally known as “Tenggek Burung” or “Cabang Tiga” is a tree species belonging to the Rutaceae family. M. lunu-ankenda is traditionally used to relieve symptoms of fever, revitalize the body and reduce high blood pressure. Studies have shown that the extract of M. lunu-ankenda contains antioxidants and anti-inflammatory properties. The fresh seeds have difficulty in germinating and takes more than 7 months to germinate. Studies need to be carried out to determine the cause of this delay in germination of M. lunu-ankenda seeds. For the first part, flower tagging was carried out in the first week of June 2014. Fruits were collected at random from the labeled panicles during each harvest (42, 56, 63, 70 and 77 days after tagging). Shape, size, colour and characteristics of the seed coat was documented. Seeds were tested for fresh weight, dry weight and moisture content (%). 50 seeds from each stage were germinated on 5 different types of media (Sand, Soil Mixture, Peat Soil, Peat Moss and Filter Paper). For the second part of the study, mature seeds harvested at day 77 after flowering were subjected to physical and chemical treatments as follows: (1) Soaked in distilled water for 12, 24 and 36 hours. (2) Scarified using sand paper for 1, 2 and 3 minutes. (3) Soaked in 98% Sulfuric acid for 10, 15 and 30 seconds. (4) Soaked in 200 ppm, 400 ppm and 600 ppm concentration of GA3 for 10 minutes. (5) Soaked in 0.2%, 0.4% and 0.6% concentration of KNO3 for 10 minutes. Imbibition rate for scarified seeds were tested in comparison to fresh seeds. Seeds were then stored in different temperatures (29 ºC, 15 ºC and 10 ºC) for six months. Germination percentage were recorded every two months after storage. Results for the first part showed that the the maximum dry weight per 100 seed (1.523 g) was recorded at 70 days after anthesis where fruit pods were dark green in colour while the seeds were black and fully developed. Moisture content percentage of seeds during dehiscence was recorded at 8.6%. Seeds obtained on day 70 and 77 showed the ability to germinate after 90 days with a percentage of 28.5% and 61.5%, respectively on peat soil. For the second part of the experiment, seeds scarified using sand paper for two minutes showed the highest germination percentage with 83%. Germination starting time was also reduced from 90 days to 20 days after sowing. Scarified seeds had a significantly higher imbibition rate in the first 12 hour compared to normal seeds. When the imbibition period reached 12 hours, scarified seeds achieved maximum water imbibition (0.381 g) compared to normal seeds which only imbibed 0.035 grams of water. After 6 months of storage, highest germination percentage and germination index was recorded when seeds were stored at 29°C, 79.5 % and 1.374, respectively. In conclusion, Melicope lunu-ankenda seeds exhibit physical seed dormancy that can be overcome by mechanical scarification of the seed coat. Of all the dormancy breaking techniques tested, it is recommended that the seeds are scarified using sand paper for two minutes. The most suitable media to germinate the seeds is peat soil. Seeds must be harvested at 77 days after flowering in order to obtain the highest germination percentage. Since mature seed naturally has a moisture content of 8.6% and can be stored until 6 months, seeds storage behaviour can be catagorised as orthodox.